ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA KONTEKSTUAL MATERI KEKONGRUENAN DAN KESEBANGUNAN - Rahmah Fadilah; Martin Bernard (IKIP Siliwangi, 2021)
This study is a qualitative descriptive study that aims to determine the forms of mistakes who made by students in solving contextual mathematical problems related to congruence and similarity. The subjects in this study were 28 students of IX K at SMP Negeri 1 Pasawahan. The data collection method was carried out through a written test consisting of 5 (five) items of description and interviews on selected subjects. Data analysis used refers to Newman's analysis consisting of 5 (five) error stages of reading problems, comprehension problems, problem transformation, process skills, and encoding. From the results it was found that the mistake who made by students is 23,6% reading error, 51,4% comprehension error, 32,1% transformation error, 13,6% process skill error, and 50% encoding error.